THE INFLUENCE OF PRONUNCIATION INSTRUCTION ON SPEAKING SKILL OF COLLEGE STUDENTS - Fani Triani Rahmat; Ateng Kurnia; Amir Hamzah (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
This paper is titled "Effect of Pronunciation Instructions on Student Speaking Skills". The aim is to know clearly the effect on students' pronunciation in English speaking skills. The research design that will be used is qualitative and data collection in case studies, using several types of data collection namely questionnaires and interviews. As a participant, the authors prepared 6 students as participants to participate in the study. These are English students from the Indonesian Institute of Education (IPI). Then the authors observe the effect on English speaking skills and what difficulties students have when learning pronunciation. The factors that cause the teaching of pronunciation are not student skills, namely the lack of practice instructed by the teacher. And the lack of students understanding books recommended by teachers to better understand the instructions given